2018
DOI: 10.7249/rr2532
|View full text |Cite
|
Sign up to set email alerts
|

Violent and Antisocial Behaviour at Football Events: Review of interventions

Abstract: For more information on this publication, visit www.rand.org/t/RR2532Published by the RAND Corporation, Santa Monica, Calif., and Cambridge, UK © Copyright 2018 RAND Corporation R® is a registered trademark.RAND Europe is a not-for-profit research organisation that helps to improve policy and decision making through research and analysis. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. Limited Print and Electronic Distribution RightsThis document and trademark(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This represents a major gap and means that there is insufficient evidence to draw any conclusions about the impact or effectiveness of the measures listed above, or other strategies that might have been employed in the region. Another literature review conducted as part of this study found more evidence about the effectiveness of interventions to prevent or respond to violent and antisocial behaviour in the European context (Taylor et al 2018).…”
Section: What Approaches Have Been Taken To Prevent and Respond To VImentioning
confidence: 87%
See 3 more Smart Citations
“…This represents a major gap and means that there is insufficient evidence to draw any conclusions about the impact or effectiveness of the measures listed above, or other strategies that might have been employed in the region. Another literature review conducted as part of this study found more evidence about the effectiveness of interventions to prevent or respond to violent and antisocial behaviour in the European context (Taylor et al 2018).…”
Section: What Approaches Have Been Taken To Prevent and Respond To VImentioning
confidence: 87%
“…Opinions are often expressed in the media about the best way to approach this issue, but there is little rigorous information on which to build an evidence-based response. Without further research, it is unclear how far lessons from the wider literature on evaluations, for instance those outlined in the review produced by RAND Europe as part of this project (Taylor et al 2018), are generalisable to this region.…”
Section: What Gaps Are There In the Literature And How Can The Evidenmentioning
confidence: 99%
See 2 more Smart Citations
“…Taylor et al (2018). This review only included journal articles published after 2005.67Adang(2011);Frosdick & Marsh (2005).68 Hylander, I & K. Granström (2010); Rosander & Guva (2012); Schreiber & Adang (2010a, 2010b).…”
mentioning
confidence: 99%